Difficulties in the Management of a Pregnancy on a Bicornuate Uterus Unicollis in Underprivileged Areas (Cameroon) - Talom , Armand Kamga; Essiben, Felix; Ombaku, Kingsley Sama; Ako, Forbang; Meka , Esther Ngo Um (New Horizons in Medicine and Medical Research Vol. 12, 2022)
A bicornuate uterus is a common congenital uterine abnormality that is generally asymptomatic. Its diagnosis is primarily parclinical with the help of imaging techniques. In certain situations, it may require reconstructive surgery the purpose of this paper is to highlight the diagnostic complexity as well as the therapeutic and prognosis elements of this case. The case of a young girl carrying a pregnancy on an undetected unicollis bicornuate uterus, which was initially classified as an unruptured ectopic pregnancy, is presented here. The bicornuate uterus continues to provide diagnostic challenges, particularly in disadvantaged populations where diagnostic resources are limited.